1999
DOI: 10.1128/mcb.19.9.6297
|View full text |Cite
|
Sign up to set email alerts
|

The Ras Mutant D119N Is Both Dominant Negative and Activated

Abstract: The introduction of mutation D119N (or its homolog) in the NKxD nucleotide binding motif of various Ras-like proteins produces constitutively activated or dominant-negative effects, depending on the system and assay. Here we show that Ras(D119N) has an inhibitory effect at a cell-specific concentration in PC12 and NIH 3T3 cells. Biochemical data strongly suggest that the predominant effect of mutation D119N in Ras-a strong decrease in nucleotide affinity-enables this mutant (i) to sequester its guanine nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 60 publications
6
63
0
2
Order By: Relevance
“…This supports observations by us and others that the mutation of the P-loop Ser/Thr in the GxxxxGKS/T motif does not necessarily, as generally assumed, reflect an exclusive binding of GDP [24,27]. In general it should be kept in mind that the corresponding mutation, T30N in Arl2, destabilizes G proteins and also strongly affects the binding to effectors, as shown for Ras, where the S17N mutation no longer bind effector molecules [28,29].…”
Section: Discussionsupporting
confidence: 89%
“…This supports observations by us and others that the mutation of the P-loop Ser/Thr in the GxxxxGKS/T motif does not necessarily, as generally assumed, reflect an exclusive binding of GDP [24,27]. In general it should be kept in mind that the corresponding mutation, T30N in Arl2, destabilizes G proteins and also strongly affects the binding to effectors, as shown for Ras, where the S17N mutation no longer bind effector molecules [28,29].…”
Section: Discussionsupporting
confidence: 89%
“…Thus, the inhibition of membrane traffic by dominantnegative RAB-D1 in tobacco leaf epidermis or Arabidopsis seedlings could be substantially restored by coexpressing wild-type c and e). Note that the RAB-D2a [N121] mutant is not significantly overexpressed under these conditions and that it accumulates less efficiently than the wild type, consistent with previous observations that small GTPases are unstable in the nucleotide-free state when not bound to the exchange factor (Okkonen and Stenmark, 1997;Cool et al, 1999).…”
Section: Discussionsupporting
confidence: 72%
“…Dominant-negative Rab GTPase mutants inhibit membrane trafficking by titration of an essential interacting partner such as a nucleotide exchange factor (Jones et al, 1995;Olkkonnen and Stenmark, 1997;Walch-Solimena et al, 1997;Cool et al, 1999;Goh et al, 2007). If this interactor has additional activities that are independent of its interaction with the mutated Rab GTPase, the effects of the dominant-negative mutant might not reflect the true activity of the Rab GTPase.…”
Section: Rab-d1 and Rab-d2a Act In Er-golgi Traffic Via Different Intmentioning
confidence: 99%
“…Single amino-acid substitutions in these positions (116-119) generated by site-directed mutagenesis result in a reduction in binding affinity for GTP (Clanton et al, 1986;Walter et al, 1986). It has been suggested that Ras (D119N) behaves as an activated mutant because of the strongly reduced nucleotide affinity enabling the mutant to bind GTP in a GEF-independent manner (Cool et al, 1999). Since the physiological concentrations of GTP and GDP are thought to be in the ratio of 25 : 1 (Walter et al, 1986), this increased exchange rate is proposed to favor the formation of the active GTP-bound form of Ras protein.…”
Section: Discussionmentioning
confidence: 99%